THE FIRST NATO MISSION TO AFRICA: DARFUR - Segell, Glen (Scientia Militaria - South African Journal of Military Studies, 2011)
NATO answered a call for assistance from the African Union (AU) in their AMIS mission in the Darfur region of Sudan in April 2005, providing airlift and training in conjunction with the European Union until the end of the mission in December 2007. This was the first time that NATO entertained a task on the African continent. NATO undertook the mission on humanitarian grounds without invoking any treaty and without any member state’s security being under any direct threat. This was a milestone in NATO’s history, and it provides a case to understanding regional alliances, regionalism and the development of trans-regionalism.